Global strain and dyssynchrony of the single ventricle predict adverse cardiac events after the Fontan procedure: Analysis using feature-tracking cine magnetic resonance imaging. Issue 2 (February 2019) - Ishizaki, Umiko; Nagao, Michinobu; Shiina, Yumi; Inai, Kei; Mori, Hiroki; Takahashi, Tatsunori; Sakai, Shuji
Highlights: Strain analysis by feature tracking magnetic resonance imaging for 100 patients after Fontan procedure. Prediction of major adverse cardiac events (MACE) at late phase of Fontan procedure. Global longitudinal strain (GLS) and the dyssynchrony index for single ventricle. GLS and the dyssynchrony index: independent predictors of MACE. Incremental information for risk stratification. Abstract: Background: The aim of this study was to determine whether major adverse cardiac events (MACE) during the late phase of the Fontan procedure could be predicted by strain measurements of single ventricles using cardiac magnetic resonance imaging with feature tracking (CMR-FT). Methods: One hundred adolescent patients who underwent the Fontan procedure (mean age, 21 years) were examined retrospectively with CMR-FT to assess the systemic single-ventricle function. Vertical long-axis cine imaging was divided into six myocardial segments. Global longitudinal strain (GLS) was determined by averaging the peak strain values of each of the six segments. The dyssynchrony index was defined as the standard deviation of the time to peak strain for six segments. The primary outcome was MACE, defined as cardiac death and unscheduled hospitalization. Results: MACE occurred in 18 patients during a mean follow-up of 62 months. According to the multivariate logistic regression analysis results for potential predictor variables, GLS and the dyssynchrony index are independent predictors of MACE. Patients with GLS ≥11.8% had significantly higher MACE-free rates than did those with GLS <11.8% [log-rank value, 14.15; p  = 0.0002; hazard ratio, 6.82; 95% confidence interval (CI), 2.51–18.56]. Patients with a dyssynchrony index <63.5 ms had significantly higher MACE-free rates than did those with dyssynchrony index ≥63.5 ms (log-rank value, 28.17; p  < 0.0001; hazard ratio, 21.69; 95% CI, 6.96–67.56). Conclusion: GLS and the dyssynchrony index found using CMR-FT are independent predictors of MACE for adolescent patients after the Fontan procedure and provide information regarding risk stratification beyond clinical parameters and biomarkers.